MODEL PENGUKURAN KINERJA PADA PERUSAHAAN DAERAH AIR MINUM SURYA SEMBADA KOTA SURABAYA - Jannah, Ely Uzlifatil; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the description of the model of performance measurement at PDAM SuryaSembada Kota Surabaya. The documentation and interview are used as the data collection technique, meanwhilethe descriptive qualitative method is used as the data analysis technique.The results of the analysis and thediscussions show that: the financial perspective has obtained good companyâs performance; the customerperspective, the implementation of vision and mission which are related to the enhancement of customersatisfaction has improved.The measurement of the internal business process perspective shows an improvedperformance. Meanwhile, the growth and learning perspective of growth and learning well performance.Eventhough, the performance of the company which is based on four perspective show well performance, thedevelopment of relevant performance measurement model is required. It is in line with the dynamic of businessenvironment in the future.Keywords: Financial Performance, Customer Perspective, Internal Business Process Perspective, Growthand Learning Perspective.